Requirements engineering - Hull, Elizabeth (Springer, 2011)
Using the latest research and driven by practical experience from industry, the third edition of this popular book provides useful information to practitioners on how to write and structure requirements. Explains the importance of Systems Engineering and the creation of effective solutions to problems ; Describes the underlying representations used in system modelling and introduces the UML2 ; Considers the relationship between requirements and modelling ; Covers a generic multi-layer requirements process ; Discusses the key elements of effective requirements management Explains the important concept of rich traceability In this third edition the authors have updated the overview of DOORS to include the changes featured in version 9.2. An expanded description of Product Family Management and a more explicit definition of Requirements Engineering are also included. Requirements Engineering is written for those who want to develop their knowledge of requirements engineering, whether practitioners or students.